Autophagy-Enhancing Drug Promotes Degradation of Mutant α₁-Antitrypsin Z and Reduces Hepatic Fibrosis - Hidvegi, Tunda; Ewing, Michael; Hale, Pamela; Dippold, Christine; Beckett, Caroline; Kemp, Carolyn; Maurice, Nicholas; Mukherjee, Amitava; Goldbach, Christina; Watkins, Simon; Michalopoulos, George; Perlmutter, David H (Science (American Association for the Advancement of Science), 2010)
In the classical form of α₁-antitrypsin (AT) deficiency, a point mutation in AT alters the folding of a liver-derived secretory glycoprotein and renders it aggregation-prone. In addition to decreased serum concentrations of AT, the disorder is characterized by accumulation of the mutant α1-antitrypsin Z (ATZ) variant inside cells, causing hepatic fibrosis and/or carcinogenesis by a gain-of-toxic function mechanism. The proteasomal and autophagic pathways are known to mediate degradation of ATZ. Here we show that the autophagy-enhancing drug carbamazepine (CBZ) decreased the hepatic load of ATZ and hepatic fibrosis in a mouse model of AT deficiency-associated liver disease. These results provide a basis for testing CBZ, which has an extensive clinical safety profile, in patients with AT deficiency and also provide a proof of principle for therapeutic use of autophagy enhancers.